Industrial Scale Production and Characterization of a Whey Fraction Enriched in Extracellular Vesicle Material - Søren Roi Midtgaard; Maria Stenum Hansen; Nikolaj Drachmann; Xiaolu Geng; Kristine Ingrid Marie Blans; Manja Mahmens Fabricius Møbjerg; Anny F. Frølund; Jan Trige Rasmussen; Marie Stampe Ostenfeld (Journal of Extracellular Biology)
ABSTRACT Human milk serves the sole nutritional role for the developing infant. During lactation, nano‐sized extracellular vesicles (EVs) in milk containing a multitude of biologically active components are transferred from mother to offspring. Infant formula (IF) based on cow milk‐derived ingredients has been reported to contain reduced levels of EVs as compared to human milk. There is therefore an unmet need to produce large‐scale volumes of milk EVs to improve IF composition. Here, we report a scalable industrial production protocol for a bovine whey‐derived ingredient that is highly enriched in EV material using a large‐scale sequential ceramic membrane filtration setup. Furthermore, we demonstrate a robust and generally applicable analytical approach to determine the relative contributions of EVs and milk fat globule membrane (MFGM) using molar ratios of the membrane‐bound proteins butyrophilin (BTN) and CD9 as surrogate markers for MFGM and EVs, respectively. Taken together, our findings provide a basis for comparing bovine milk‐containing foods and aid in developing specialized ingredients that can minimize the compositional difference between infant formula and human milk.